The relationship between number talks and ambitious instruction: learning from beginning teachers - Pak, Byungeun; Cavanna, Jillian M.; Jackson, Brent E. (Mathematical thinking and learning, 2025)
Number talks offer one way for beginning teachers to engage in ambitious instruction (Lampert et al., 2010) that fosters students' conceptual understanding. This paper explores: (1) features of the number talk routine and (2) how beginning teachers' enactment of number talks are aligned with ambitious instruction. The authors utilized Cazdan's (2001) sequential and selectional dimensions to systematically analyze videos of 17 number talks enacted by seven beginning teachers. Findings indicate that the number talk routine consisted of introducing, collecting, idea sharing, and closing phases. Additionally, using the M-Scan instrument (Berry et al., 2013) to measure whether lessons were ambitious, the authors found that more ambitious lessons included number talks where teachers supported multiple students to engage in another student's strategy rathter than simply shaing individual strategies. We discuss several important implications for mathematics teacher education and research on ambitious mathematics instruction.